Should major depressive disorder with mixed features be classified as a bipolar disorder? - LIU, Xiaohua (Shanghai Arch Psychiatry, 2014)
The new diagnostic category in the Depressive Disorders chapter of DSM-5 entitled ‘Major Depressive Disorder With Mixed Features’ is applied to individuals who meet criteria for Major Depressive Disorder and have concurrent subsyndromal hypomanic or manic symptoms. But the operational definition of this new specifier is much closer to that of hypomania and mania than to the definition of atypical depression or the older ‘mixed depression.’ Moreover, multiple studies have shown that the characteristics of individuals with this condition and the clinical trajectory of their illness is much closer to that of bipolar patients than to that of depressed individuals without comorbid hypomanic or manic symptoms. Thus we believe that this condition would be more appropriately placed in the Bipolar Disorders chapter of DSM-5. We also believe that this blurring of the depressive disorder- bipolar disorder boundary is one cause for the low inter-rater reliability in the diagnosis of Major Depressive Disorder.